Carotid blowout syndrome after reirradiation for head and neck malignancies: a comprehensive systematic review for a pragmatic multidisciplinary approach. (November 2020) - Alterio, Daniela; Turturici, Irene; Volpe, Stefania; Ferrari, Annamaria; Russell-Edu, Samuel William; Vischioni, Barbara; Mardighian, Dikran; Preda, Lorenzo; Gandini, Sara; Marvaso, Giulia; Augugliaro, Matteo; Durante, Stefano; et al.
Abstract: Aim: To provide a literature review on risk factors and strategies to prevent acute carotid blowout (CBO) syndrome in patients who underwent reirradiation (reRT) for recurrent head and neck (HN) malignancies. Patients and Methods: Inclusion criteria were: 1) CBO following reRT in the HN region, 2) description on patient-, tumor- or treatment-related risk factors, 3) clinical or radiological signs of threatened or impending CBO, and 4) CBO prevention strategies. Results: Thirty-five studies were selected for the analysis from five hundred seventy-seven records. Results provided indications on clinical, radiological and dosimetric parameters possibly associated with higher risk of CBO. Endovascular procedures (artery occlusion and stenting) to prevent acute massive hemorrhage in high risk patients were discussed. Conclusion: Literature data are still scarce with a low level of evidence. Nevertheless, the present work provides a comprehensive review useful for clinicians as a multidisciplinary pragmatic tool in their clinical practice.